Delivery, setting and outcomes of paediatric Outpatient Parenteral Antimicrobial Therapy (OPAT): a scoping review. Issue 11 (15th November 2018) - Carter, Bernie; Carrol, Enitan D; Porter, David; Peak, Matthew; Taylor-Robinson, David; Fisher-Smith, Debra; Blake, Lucy
Abstract : Background: There has been little detailed systematic consideration of the delivery, setting and outcomes of paediatric Outpatient Parenteral Antimicrobial Therapy (OPAT), although individual studies report that it is a safe and effective treatment. Objective: This scoping review aimed to examine what is known about the delivery, settings and outcomes of paediatric OPAT and to identify key knowledge deficits. Design: A scoping review using Arksey and O'Malley's framework was undertaken. Data sources: Keywords were identified and used to search MEDLINE and CINAHL. Study appraisal methods: Primary research studies were included if samples comprised children and young people 21 or under, who had received OPAT at home or in a day treatment centre. The Mixed Methods Appraisal Tool was used to review the methodological quality of the studies Main findings: From a preliminary pool of 157 articles, 51 papers were selected for full review. 19 studies fitted the inclusion criteria. Factors influencing delivery of OPAT were diverse and included child's condition, home environment, child-related factors, parental compliance, training and monitoring. There is little consensus as to what constitutes success of and adverse events in OPAT. Conclusions: Future studies need to clearly define and use success indicators and adverse events in order to provide evidence that paediatric OPAT is safe and effective. Implications: Consensus outcomes that include child and parent perspectives need to be developed to allow a clearer appreciation of a successful paediatric OPAT service.